2003
DOI: 10.17221/4186-pse
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and germination of Shaggy soldier (Galinsoga ciliata Blake.) and Common lambsquarter (Chenopodium album L.)

Abstract: Laboratory experiments were carried out with seeds of Galinsoga ciliata and Chenopodium album in 1998, 2000 and 2001. The study involved germination of non-dormant seeds in the light and the dark at 5-30°C, the germination energy at 15, 24, and 33°C, and the primary dormancy of seeds matured during the period from July to October. Both weeds germinated better in the light compared to the dark. Seeds of G. ciliata germinated at 10-33°C. Germination exceeding 85% was recorded at 12-28°C. Ch. album germinated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 8 publications
5
18
0
Order By: Relevance
“…The observed greater recruitment of seedlings of Galinsoga sp. in circular gaps with considerable light intensity corresponds to the findings of other authors [56][57][58] who documented that seeds of Galinsoga ciliata and G. parviflora are positively photoblastic. Additionally, the substantial recruitment of Cirsium arvense, Tussilago farfara, Chenopodium album, Lysimachia vulgaris, Betula pendula and Sonchus arvensis in round gaps might be due to partial or absolute requirements of light for initiating and completing the germination process [59].…”
Section: Recruitment Rates Of Particular Species In Differently Shapesupporting
confidence: 90%
“…The observed greater recruitment of seedlings of Galinsoga sp. in circular gaps with considerable light intensity corresponds to the findings of other authors [56][57][58] who documented that seeds of Galinsoga ciliata and G. parviflora are positively photoblastic. Additionally, the substantial recruitment of Cirsium arvense, Tussilago farfara, Chenopodium album, Lysimachia vulgaris, Betula pendula and Sonchus arvensis in round gaps might be due to partial or absolute requirements of light for initiating and completing the germination process [59].…”
Section: Recruitment Rates Of Particular Species In Differently Shapesupporting
confidence: 90%
“…This negative influence on C. album seedlings growth can be interpreted similarly to the negative influence on germination. Moreover, C. album is a lightdemanding species (Jursík et al 2003;Tang et al 2008) growing in the open landscape. This species is probably adapted to different soil parameters than coniferous forest can provide.…”
Section: Discussionmentioning
confidence: 99%
“…Its seeds are dormant and their germination is gradual (Baskin & Baskin 1977;Grime et al 1981). The optimum condition for useful germination of C. album is low temperature storage and light condition during the germination (Jursík et al 2003;Tang et al 2008). In contrast to crop or arable plants, the percentage of germinated C. album seeds is usually markedly under 100 %, which predetermines it for a research of seed germination stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ivany and Sweet (), Jursik et al . () and Damalas (), minimum temperature for germination is 10°C. In our experiments, optimal alternating temperature regime for germination of Galinsoga spp.…”
Section: Discussionmentioning
confidence: 99%
“…(), but contradict findings of Jursik et al . () who found that G. quadriradiata seeds were primary dormant for 10 to 100 days, depending on time of seed ripening; seeds that ripened early in the season (July) showed longest dormancy duration. In our study, fresh seeds were harvested in autumn, which may explain the lack of primary dormancy.…”
Section: Discussionmentioning
confidence: 99%